Hubungan Pengetahuan dan Sikap Dengan Kepemilikan Jamban di Desa Silale Kecamatan Nusaniwe - Friska Senda Tehupurung; Sunik Cahyawati; Herlien Sinay; Edi Sugiarto (Lembaga Pengembangan Kinerja Dosen, 2024)
According to Letementira (2020), a latrine is a safe and comfortable place for defecation or the disposal of feces, designed to prevent contamination of water bodies and avoid unpleasant odors. The World Health Organization (WHO) reported in 2019 that globally, 892 million people still practice open defecation. The Indonesian Ministry of Health's website reveals that, as of January 2020, there are still 8.6 million households in the country where family members practice open defecation (Ministry of the Republic of Indonesia, 2020). This research aims to determine the relationship between knowledge, attitudes, and latrine ownership in Silale Village, Nusaniwe Subdistrict. The total population of the village, consisting of 75 respondents, was used as the sample for this study, and total sampling was applied. The research instruments included questionnaires, and data analysis was conducted using SPSS software with a chi-square test for statistical analysis. The results showed a significant relationship between knowledge, attitudes, and latrine ownership, with a p-value of 0.000. This indicates that both knowledge and attitude are closely related to the ownership of latrines in the study area. These findings suggest that improving public knowledge and attitudes toward sanitation practices could play a crucial role in promoting latrine ownership and ultimately reducing open defecation practices in Silale Village.